PEMEROLEHAN KALIMAT DALAM BAHASA MELAYU SAMBAS PADA ANAK USIA 4 TAHUN (STUDI KASUS: MUHAMMAD AL FATIH DAN RIFA NUR AZKYA) - Alisa, Nur; Sulissusiawan, Ahadi; Jupitasari, Mellisa (Universitas Tanjungpura, 2025)
This research aims to describe the acquisition of sentences in Malay Sambas in 4 years old children (Case Study: Muhammad Al-Fatih and Rifa Nur Azkiya). The method used in this research is descriptive method. The form of research is qualitative. The source of research data is the speech of Muhammad Al Fatih and Rifa Nur Azkya in the form of sentences. The data in this research are the speech of the two subjects. Data collection techniques are, tapping, listening, engaging, recording, and taking notes. Data collection tools are gadgets and note sheets. The results of research on the aspect of sentence acquisition in Malay sambas show that: There were declarative sentences (news) found, imperative (command) sentences, interrogative (question) sentences and exclamative (exclamation) sentence. Meanwhile, Rifa Nur Azkya can be classified as declarative sentences (news). Imperative (command) sentences, interrogative (question) sentences and exclamative (exclamation) sentences. Based on data classification, the sentence structure patterns in Malay sambas obtained by Muhammad Al Fatih are: (S-P), (S-P-O), (S-P-Pel), (S-P-Ket), (S-PO-Ket), (P-S), (P-S-Pel), (PS-Ket), (Ket-S-P), Pel-S-P, and (Pel -P-S). Meanwhile, based on data classification, the Sambas dialect Malay sentence structure patterns obtained by four years old child Rifa Nur Azkya include: (S-P), (S-P-O), (S-P-Pel), (S-P-Ket), (S-P-O-Pel), (SP-O-Ket), (P-S), (Ket-P-S), (Ket-S-P), (Pel-S-P), and (P-S-Ket). Based on the semantic role of Muhammad Al-Fatih's and Rifa Nur Azkya sentence elements, they include as perpetrator, target, experiencer, as luck, as attribute, and as description of the entire sentence obtained based on the chosen theory.